Validation of three age based weight formulae for estimating weight among Indian children - Sharma, Saurabh; Feroz, Shah Huzaifa; Yadav, Jeetendra; Rao, M. Vishnu Vardhana (International Journal Of Community Medicine And Public Health, 2023)
Background: Weight estimation in paediatric emergencies is often required to calculate drug dosages, fluid therapy and defibrillation. The ‘gold standard’ of actually weighing the patient is not practically possible in emergency conditions. Many formulae have been developed in an attempt to accurately estimate a child’s weight using age like advanced paediatric life support (APLS), Luscombe, and Argall’s modification. However, these formulae might not be applicable in the Indian context. This study aims is to validate standard age-based formulae (APLS, Luscombe, and Argall’s) and their accuracy in estimating the weight of Indian children. Methods: The study used secondary data from the fourth round of the National Family Health Survey (2015-16). The estimated weights as computed by the APLS guidelines, the Luscombe and the Argall formulae were compared to their respective measured weights during the survey. Results: All three formulae (APLS, Luscombe, and Argall) overestimated the weights. The APLS formula exhibited the least weight difference among the different age groups (-3.51±2.08 kg). The average percentage difference between the estimated weights using the APLS, Luscombe, and Argall formula and the actual weights was 23%, 38%, and 28%, respectively. Conclusions: All the three age-based weight formulae, namely APLS, Argyll, and Luscombe, overestimated the weight among the Indian children, clearly showing the need to adjust the formulae for accurate weight estimation of Indian children.